ANALISIS PERENCANAAN PRODUKSI STUDI PADA PT. PRIMISSIMA (PERSERO) - , MUHAMMAD HASNAN AMIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Planning is one of the most important parts of running a business. Good effort in the field of businesses that produce goods or engaged in services. Both have to pay attention to important elements such as planning. In conducting the business of manufacturing production planning are closely linked. Thus production planning becomes something that can not be left in the business manufacturing. The research take the example of the problems that occurred in one of the textile companies in the Yogyakarta region, namely PT. Primissima. This study is more Qualitative research for analyzing phenomena occurring within a company. Analysis of the observed are the factors that influence the production planning. Resulting factors that cause the difference between planned and actual production. The processed data is the primary data is the primary data source and secondary data to support the analysis. By using data analysis tools such as fishbone diagram then found six factors contributing to the difference between planned and actual production. These six factors are (1) Restructuring poor management is effective